2011
DOI: 10.1007/s00429-011-0375-0
|View full text |Cite
|
Sign up to set email alerts
|

Brainpeps: the blood–brain barrier peptide database

Abstract: Peptides are able to cross the blood-brain barrier (BBB) through various mechanisms, opening new diagnostic and therapeutic avenues. However, their BBB transport data are scattered in the literature over different disciplines, using different methodologies reporting different influx or efflux aspects. Therefore, a comprehensive BBB peptide database (Brainpeps) was constructed to collect the BBB data available in the literature. Brainpeps currently contains BBB transport information with positive as well as neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 197 publications
(386 reference statements)
1
49
0
Order By: Relevance
“…For the first model using The BBB-influx classification system for peptides as proposed by Stalmans et al (2015b) indicated that BEA and ENNs are located in class 5, corresponding to a very high brain influx, which was also confirmed by comparing our obtained influx data of BEA/ENNs with those of other peptides (Van Dorpe et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…For the first model using The BBB-influx classification system for peptides as proposed by Stalmans et al (2015b) indicated that BEA and ENNs are located in class 5, corresponding to a very high brain influx, which was also confirmed by comparing our obtained influx data of BEA/ENNs with those of other peptides (Van Dorpe et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…A large number of peptides like insulin [2], cyclosporine [3], corticotropin [4] are used for treating various diseases like diabetes and immunoregulatory disorders [57]. Owing to their immense therapeutic importance, peptides have been curated from literature and stored in form of databases such as Hemolytik [8], PhytAMP [9], APD2 [10], DAMPD [11], CAMP [12], YADAMP [13], CPPsite [14], TumorHoPe [15], Quorumpeps [16], Brainpeps [17], MilkAMP [18], DADP [19], LAMP [20] and AVPdb [21] to name a few. Also, a number of computation tools such as CellPPD [22], TumorHPD [23], AntiCP [24], AVPpred [25] and ToxinPred [26] have been developed to predict and design cell penetrating, tumor homing, anticancer, antiviral and toxic peptides, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies were promising and raised a hope for the fight against these devastating diseases. Keeping in mind the huge pharmacological importance of therapeutic peptides, many databases of therapeutic peptides have been developed so far that include CPPsite (24), APD2 (13), CAMP (12), Brainpeps (25), Quorumpeps (26), TumorHope (27), Hemolytik (28) and DAMPD (14). However, no attempt has been made to catalog APPs and to understand the properties of these peptides.…”
Section: Discussionmentioning
confidence: 99%